2006
DOI: 10.1182/blood-2005-10-4025
|View full text |Cite
|
Sign up to set email alerts
|

The antiapoptotic gene A1/BFL1 is a WT1 target gene that mediates granulocytic differentiation and resistance to chemotherapy

Abstract: Previous work has demonstrated that WT1 (؊Ex5/؊KTS) potentiates granulocyte colony-stimulating factor (G-CSF)-mediated granulocytic differentiation. This WT1 isoform suppresses cyclin E, which may contribute to the prodifferentiation effect by slowing proliferation, but WT1 target genes that affect survival might also be involved. We screened a cDNA array and identified the bCL2 family member A1/BFL1 as a new WT1 target gene in 32D cl3 murine myeloblast cells. Induction of WT1 (؊Ex5/؊KTS) expression is accompa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 27 publications
0
43
0
Order By: Relevance
“…In addition to NFB, other transcription factors have been implicated in the transcriptional regulation of Bfl-1. These include all-trans retinoic acids in leukemia cells 401 , retinoic X receptor agonists in naïve T lymphocytes 402 , and the transcription factors WT-1 403 and PU.1 404 . On the other hand, Bfl-1 transcription has also been observed to be blocked by the transcription factor Blimp-1 in plasma cells 405 .…”
Section: The Regulation Of Bfl-1mentioning
confidence: 99%
“…In addition to NFB, other transcription factors have been implicated in the transcriptional regulation of Bfl-1. These include all-trans retinoic acids in leukemia cells 401 , retinoic X receptor agonists in naïve T lymphocytes 402 , and the transcription factors WT-1 403 and PU.1 404 . On the other hand, Bfl-1 transcription has also been observed to be blocked by the transcription factor Blimp-1 in plasma cells 405 .…”
Section: The Regulation Of Bfl-1mentioning
confidence: 99%
“…44 In addition to antiapoptotic genes, WT1 directly modulates the expression of genes that encode components of the cell cycle apparatus, such as cyclin E, which co-regulates the G1/S-phase transition. 42 The recently described AML-related CTA cyclin A1 has also been implicated in the G1/S-phase regulation. 33 Other LAAs, including AurA, 32 cyclin B1, 45 M-phase phosphoprotein 11 (MPP11), 36 NuSAP1, 46 SSX2IP 36 and RHAMM, 36 are predominantly involved in regulating the G2/M transition or the mitotic phase of the cell cycle.…”
Section: Criterion 3: Oncogenicitymentioning
confidence: 99%
“…These studies, including WT1 peptide and WT1-targeted dendritic cell vaccine trials, have unequivocally established that CD8 þ T-cell immune responses specific to WT1 can be induced by active immunization in a substantial number of AML patients. 14 In those patients, multiple WT1 CTL epitopes have been recognized as immunogenic (including WT1 [37][38][39][40][41][42][43][44][45] , WT1 [126][127][128][129][130][131][132][133][134] , WT1 [187][188][189][190][191][192][193][194][195] and WT1 [235][236][237][238][239][240][241][242][243] ), demonstrating the excellent in vivo immunostimulatory potential of WT1 (Table 1). 14,72 This is further supported by the capacity to induce WT1-specific CD4 þ helper T-cell immunity in patients with AML through active immunization.…”
Section: Criterion 4: Immunogenicity Humoral and Cellular Immune Respmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Our laboratory has investigated the hypothesis that different WT1 isoforms can have distinct effects on tumorigenesis. We found that induction of WT1 (ϪEx5/ϪKTS) in mammary epithelial cells causes a cell cycle arrest and expression of genes such as albumin associated with a differentiated phenotype, whereas induction of WT1 (ϩEx5/ϩKTS) results in an epithelial-to-mesenchymal transition and up-regulation of proliferation-associated genes such as B-raf (13). In the course of these investigations, we also found that WT1 (ϩEx5/ϩKTS) up-regulates vascular endothelial growth factor (VEGF) in these cells.…”
mentioning
confidence: 96%